2012
DOI: 10.1104/pp.112.212787
|View full text |Cite
|
Sign up to set email alerts
|

SAUR36, a SMALL AUXIN UP RNA Gene, Is Involved in the Promotion of Leaf Senescence in Arabidopsis      

Abstract: Small Auxin Up RNA genes (SAURs) are early auxin-responsive genes, but whether any of them are involved in leaf senescence is not known. Auxin, on the other hand, has been shown to have a role in leaf senescence. Some of the external application experiments indicated that auxin can inhibit leaf senescence, whereas other experiments indicated that auxin can promote leaf senescence. Here, we report the identification and characterization of an Arabidopsis (Arabidopsis thaliana) leaf senescenceassociated gene nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 48 publications
5
108
0
1
Order By: Relevance
“…Auxin synthesis sets in motion major changes in gene expression and physiology (Guilfoyle and Hagen, 2007), and the down-regulation of auxin synthesis and signaling can be considered a primary event in the progression of senescence. Although reports of the role of auxin in leaf senescence conflict (Quirino et al, 1999;Okushima et al, 2005;Hou et al, 2013;Jiang et al, 2014), our molecular data suggest that auxin action is down-regulated during the progression of leaf senescence.…”
Section: Discussionmentioning
confidence: 62%
“…Auxin synthesis sets in motion major changes in gene expression and physiology (Guilfoyle and Hagen, 2007), and the down-regulation of auxin synthesis and signaling can be considered a primary event in the progression of senescence. Although reports of the role of auxin in leaf senescence conflict (Quirino et al, 1999;Okushima et al, 2005;Hou et al, 2013;Jiang et al, 2014), our molecular data suggest that auxin action is down-regulated during the progression of leaf senescence.…”
Section: Discussionmentioning
confidence: 62%
“…In addition to ESP/ESR, AtERF4 and AtERF8 negatively regulate the expression of many genes, including AUX/IAA genes. Several studies have reported on both the positive and the negative roles of auxin in the progression of leaf senescence (Ellis et al, 2005;van der Graaff et al, 2006;Hou et al, 2013). Because IAA3/ SHY2 suppresses expression of auxin-inducible genes through physical interactions with AUXIN RESPONSE FACTORs (ARFs) and several ARFs act as positive regulators of leaf senescence (Ellis et al, 2005;Weijers et al, 2005), the negative effects on IAA3/SHY2 by AtERF4 and AtERF8 may be involved in the progression of leaf senescence.…”
Section: Class II Erf Regulatory Cascade For the Progression Of Leaf mentioning
confidence: 99%
“…Previous studies have shown that ectopic expression of several SAUR family genes resulted in elongated hypocotyls in the light and that plants overexpressing SAUR19 exhibited opened cotyledons in the dark (23)(24)(25). However, several other SAURs have been suggested to inhibit cell expansion in certain organs (26)(27)(28). To test the effects of lirSAURs on plant growth, we generated transgenic lines overexpressing SAUR14, SAUR50, and SAUR65, which were selected to represent classes 1, 2, and 3, respectively.…”
Section: Saur Family Genes Exhibit Remarkably Organ-specific Light-mentioning
confidence: 99%
“…Based on microarray analysis, about half of SAURs are up-regulated by auxin treatment in Arabidopsis (22). Overexpression of several distinct SAUR genes resulted in increased growth of cotyledons, hypocotyls, or roots, respectively (23)(24)(25), whereas a few SAURs have been suggested to negatively regulate cell growth in specific organs (26)(27)(28). Recently, it has been found that SAURs could interact with D-clade type 2C protein phosphatase (PP2C) proteins to inhibit their phosphatase activities, therefore activating…”
mentioning
confidence: 99%